A study on flux declination in enzymatic membrane reactor (emr) for cyclodextrins production / A.M. Mimi Sakinah …[et al.] - A.M., Mimi Sakinah; Md Illias, Rosli; Ismail, A.F.; Hassan, Osman; Zularisamil, A.W (2006)
This paper investigated on the flux declination in ultrafiltration membrane during separation of cyclodextrins from tapioca starch and enzyme CGTase, The Resistance-In-Series Model was used to identify the responsible hydraulic resistances, The result showed that, the declination of flux was obtained as the amount of total resistances increased. The flux was decreased continuously with time until it reached a steady-state stage, In this stage, the cake layer on the membrane surface has been achieved an equilibrium thickness. These resistances can be eliminated by using hydraulic and chemical cleaning. The results show that 20% of the foulant was removed from the membrane surface after hydraulic cleaning while 27% of the foulant was desorbed from the membrane surface after chemical cleaning.